La prise en compte de la submersion marine par la loi littoral - Loïc Prieur (Éditions en environnement VertigO, 2015)
Storm Xynthia showed the flaws in the legal framework governing the urbanization along the seaside. This article analyzes the current state of the device of coastal law, cornerstone of the legal framework for the control of urbanization on coastal districts, which addresses the issue of coastal flooding only indirectly. Beyond the analysis of the existing legal provisions, the authors propose amendments to the provisions of the Coastal Act so that it integrates the problematic of marine floods, and eventually allows an effective consideration of natural hazards in the coastal planning policy.